Crisis response strategies of universities during the ongoing war: Beyond experience and responsibilities - Oleksandr Spivakovsky; Serhii Omelchuk; Daria Malchykova (Problems and Perspectives in Management)
Extraordinary threats of the large-scale stage of the Russian-Ukrainian war challenged the resilience and capability of all higher education institutions. However, their influence varied with location, infrastructure damage, internal capacity for changes and academic community resilience, external support, and solidarity initiatives. The purpose of this study is to assess the implementation of crisis management decisions and the formation of a crisis response strategy for a university in wartime (on the example of Kherson State University). The assessment draws on thematic analysis, the case method, statistical data analysis, and a survey of academic community members in 2023 (664 students and 150 staff), which focused on identifying a vision of the university’s values and strategic priorities. It showed the priorities of ensuring education quality and research, expanding international cooperation, diversifying funding, and strengthening cooperation with external stakeholders, including employers. The analysis of the university management’s actions in 2022–2024 demonstrated that the university transitioned from a resistance strategy (2022) as the first situational response to the large-scale invasion and occupation to a resilience strategy and the return to progressive development in the years ahead. The paper concludes that successful crisis management follows the key principles: flexibility, value orientation, and scaling up. It offers management guidance for developing a crisis response strategy that can be adapted to the unique needs of other universities: a comprehensive analysis of the crisis situation, crisis communication, planning of resource maintenance, and transparent and participatory decision-making for crisis management based on values and ethical implications. AcknowledgmentThis study is part of project No.101129236+DigiUni-ERASMUS-EDU-2023-CBHE). The research was partly supported by the 2024 BridgeUSA Ukrainian Academic Fellows Program, funded by the U.S. Department of State’s Bureau of Educational and Cultural Affairs (ECA), with additional funding provided by Harvard University and administered by the American Councils for International Education. The opinions expressed herein are the authors’ own and do not necessarily express the views of either the Bridge USA or American Councils.The authors express their gratitude to the vice-presidents, deans of faculties, and academic and non-academic staff of Kherson State University who participated in the development of institutional documents that implement crisis management decisions presented in this paper and form a crisis response strategy for the university during martial law.